A simple structure of the veterinary business that works with farm animals explored as an operational wheel (Veterinary Science, 2018)
An exploratory/descriptive trial with a qualitative and some quantitative approach was done through a survey to veterinarians resident in General Pico, La Pampa, who work with private farmers as customers. Ten out of one hundred and twenty-nine met these characteristics since the rest worked in connection with small animal clinic, private and public activities or just public activities. Through the information given, their companies were explored as a simple structure, describing their function as an operational wheel in search of identifying their basic strategies applied to the time of management. The analysed businesses were: the businessman, servuction as production, acquisition, commercial, personal and financial. Just one case exhibits a long-range vision of ten years, the rest did not suggest those prospects, and it was called self-businessman. Responsible registered and without a veterinary shop, he recognized and applied producers´segmentation techniques; he knew and classified his costs among financial, commercial and amortization; he also used different mechanisms to finance himself either in his own or external banks, suppliers, etc., and he finally worked with stock control among other management tools. In general, the rest of the colleagues just identified some of the former management tools, with a short-range view, focusing on technical aspects, whereas the management decision was positioned in the second place. The final analysis showed that the companies with their owners, were simples’ micro-companies, operating in simple environments with little changes since their beginnings.
Keywords: management; servuction; veterinary company; simple structure company; operational wheel